KAJIAN KESIAPAN IMPLEMENTASI MANAJEMEN MUTU TERPADU (MMT) PADA PT. XYZ BERDASARKAN EUROPEAN FOUNDATION QUALITY FOR MANAGEMENT (EFQM) - Rachel J Ompusunggu; Nazaruddin Matondang; Ikhsan Siregar (Jurnal Teknik Industri USU, 2013)
PT. XYZ is the manufacturing industry that is engaged in the processing of kitchen utensils. But in running its business, the company is still often face problems relating to the quality of product defects that eventually resulted in the number of requests could not be met. To address the problem of the quality of this, companies need to implement Total Quality Management (TQM). However, need to be examined in advance of accession the application of quality management positions in the company based on European Foundation Quality for Management (EFQM) model. The purpose of this study is to analyse the influence of each variable in EFQM in order to determine the company's readiness to implement TQM. A method of analysis in this research is path analysis. Its purpose to explain direct effect and indirect effect from exogenous variable to endogenous variablein EFQM model. The result showed that  variable of EFQM, which  need to be improved is strategy and planning on process of 14.3%. Effort which need to do by the company to improve the effect  of strategy and planning on process are making training knowledge about  company’s strategy and rules, personal approchment to the employee, and controlling the strategy and rules. Overall, the total score based on self assessment is 787.637 or approximately 78.76%, which indicates that the company is in great shape ready to implement TQM.